INDUSTRI PELAYARAN INDONESIA: PENDEKATAN DARI SUSTAINABLE MARKETING ENTERPRICE - Cahya Purnomo (Majalah Ilmiah Bahari Jogja, 2015)
The shipping industry plays a major role in world trade, especially Indonesia as an archipelagic country, has not demonstrated superiorperformance. This paper aims to propose to the Indonesian shipping industry with sustainable market-ing enterprice as marketing strategyconcept.The approach method by literature review mainly based on the marketing strategy concept of Kotler et al (2008) with meta analysis by other established iterature. Build upon comprehensive marketing strategy is expected to raise performance due to have sustainable competitive strategic.